2017
DOI: 10.1016/j.ijvsm.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of caffeine supplementation and concerted utilization of enzymatic and mechanical semen liquefaction on freezability of dromedary camel spermatozoa

Abstract: Assisted reproductive technologies have been reported to improve reproductive efficiency and genetic potential in camelids. Two experiments were carried out to determine efficiency of centrifugation in the presence of a mucolytic agent for liquefaction of dromedary semen. In the first experiment, three groups, namely: I. Tris lactose (TL, control), II. Tris lactose supplemented with amylase (TL_A) and III. Tris lactose supplemented with amylase followed by seminal plasma removal via centrifugation (TL_A_Cent.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…This is in consonance with previous results in rams [23]. Contrariwise, improved sperm acrosome integrity has been reported after caffeine inclusion in sperm diluent of buffalos [24] and camels [25].…”
Section: Discussionsupporting
confidence: 92%
“…This is in consonance with previous results in rams [23]. Contrariwise, improved sperm acrosome integrity has been reported after caffeine inclusion in sperm diluent of buffalos [24] and camels [25].…”
Section: Discussionsupporting
confidence: 92%
“…Modern breeding systems require, nowadays, the diffusion of superior genotypes and thus the selection of high quality gametes and embryos. In male reproduction, many factors such as routine procedures of handling and storage, might affect negatively the quality of spermatozoa, and several strategies have been designed to overcome these limitations in order to achieve high in vivo and in vitro fertility rates [21], [22]. Among others, sperm purification and sorting represent a valid tool for the selection of sub-populations of the best spermatozoa (in terms of motility and morphology) within an ejaculate and the discard of defective cells, contaminations and debris.…”
Section: Nanotechnologies For Sperm Purification and Sorting In Farm mentioning
confidence: 99%
“…It has been reported that Na + ions play an important role in regulation of brook trout spermatozoa activation when Ca 2+‐ free solutions were used (Bondarenko et al., 2014b). On the other hand, supplementing the sperm activator with caffeine has been shown to improve sperm motility in fresh and thawed semen of various species of mammals (Barkay et al., 1977; El‐Bahrawy, 2017; Rota et al., 2018). In rainbow trout, caffeine has increased the time of sperm motility in fresh semen to up to twice the normal value (Valdebenito, 2007).…”
Section: Discussionmentioning
confidence: 99%